Conodonts in Ordovician biostratigraphy. (3rd October 2016) - Bergström, Stig M.; Ferretti, Annalisa
Abstract : The long time interval after Pander's (1856) original conodont study can in terms of Ordovician conodont biostratigraphical research be subdivided into three periods, namely the Pioneer Period (1856–1955), the Transition Period (1955–1971) and the Modern Period (1971‐Recent). During the pre‐1920s, the few published conodont investigations were restricted to Europe and North America and were not concerned about the potential use of conodonts as guide fossils. Although primarily of taxonomic nature, the pioneer studies by Branson & Mehl, Stauffer and Furnish during the 1930s represent the beginning of the use of conodonts in Ordovician biostratigraphy. However, no formal zones were introduced until Lindström (1955) proposed four conodont zones in the Lower Ordovician of Sweden, which marks the end of the Pioneer Period. Because Lindström's zone classification was not followed by similar work outside Baltoscandia, the time interval up to the late 1960s can be regarded as a Transition Period. A milestone symposium volume, entitled 'Symposium on Conodont Biostratigraphy' and published in 1971, summarized much new information on Ordovician conodont biostratigraphy and is taken as the beginning of the Modern Period of Ordovician conodont biostratigraphy. In this volume, the Baltoscandic Ordovician was subdivided into named conodont zones, whereas the North American Ordovician succession was classified into a series of lettered or numbered faunas. Although most of the latter did not receive zone names until 1984, this classification has been used widely in North America. The Middle and Upper Ordovician Baltoscandic zone classification, which was largely based on evolutionary species changes in lineages and hence includes phylozones, has subsequently undergone only minor changes and has been used slightly modified also in some other regions, such as New Zealand, China and eastern North America. The great importance of conodonts in Ordovician biostratigraphy is shown by the fact that conodonts are used for the definition of two of the seven global stages, and seven of the 20 stage slices, now recognized within this system.